Literature Review of Occupational Safety and Health Risk Management in Foundation Work - Susanto, Tri; Nurdiana, Asri; Wibowo, M. Agung; Maromi, M. Izeul (Rekayasa Sipil, 2026)
Identifying risks in construction projects is essential for anticipating hazards and developing effective risk management measures. The intricacy of construction projects encompasses numerous aspects that can impact their effective completion, including the risk of worker accidents in the field. This study aims to identify Occupational Safety and Health (OHS) risk factors in foundation work through a literature review using the Publish or Perish application. Literature was obtained through the Google Scholar and Crossref databases, with a maximum search limit of 100 articles, and was limited to the 2020–2025 period to ensure relevance to current conditions. Search phrases used included risk management, risk identification, occupational safety and health, and foundation, with literature selected based on the suitability of the title and its relevance to the research objectives. The study findings reveal 11 potential hazards, with five predominant risks: being struck by construction materials, being impacted or ensnared by heavy machinery, falling into dig sites, sustaining puncture or laceration injuries from sharp objects, and experiencing ocular ailments due to exposure to materials or dust. These findings affirm that foundation work presents a considerable hazard, necessitating the implementation of risk control hierarchy, such as elimination, engineering methods, administrative measures, enhancement of worker safety behavior, and adaptation to contextual dynamics to fortify the safety culture in construction projects.